Caterpillar Pests of Tiki Huts and Other Thatched Structures - Stephen Henry Brown; Lyle J. Buss (EDIS)
Two species of caterpillars that eat dried sabal palm leaves have been causing problems with thatched structures. If you’ve got a chickee or are planning to get one, you can take steps to protect the thatch. Learn how to identify and manage the two caterpillar pests in this 4-page fact sheet written by Stephen H. Brown and Lyle J. Buss and published by the UF/IFAS Entomology and Nematology Department. https://edis.ifas.ufl.edu/in1213